Integration of Design for Manufacture and Assembly with Product Design in Product Design Improvement: A Systematic Literature Review - Yazid, Shishilya; Ginting, Rosnani; Panjaitan, Nismah (TALENTA Publisher, 2024)
This paper aims to investigate and analyze some previous literature relevant to the Design for Manufacture and Assembly and Design for Safety methods in international journals. An extensive review and analysis of the body of literature was conducted to discuss the findings in a few chosen papers pertaining to the application of both methods, using a survey based on descriptive and qualitative surveys published in international journals with publication period limitations from 2011 to 2023 published in proceedings and electronic journals in English. So far, there has never been any research or literature review that discusses the Integration of Design for Manufacture and Assembly with Design for Safety.